Fretting wear behaviour of MoS2 dry film lubricant - Barman, K; Voisey, K T; Shipway, P H; Pattinson, G (Tribologia - Finnish Journal of Tribology, 2015)
Dry film lubricants (DFL) are used as palliative coatings to prevent fretting wear. In this work fretting tests are carried out on coated Ti6Al4V cylinders on coated flat samples under dry sliding conditions, using an amplitude of 300 µm, 2.5 Hz frequency and 575 N normal loads. During the tests the coefficient of friction (CoF) was monitored, with tests being terminated when the coefficient of friction reached 0.7. Wear scars were analysed by profilometry and SEM to elucidate wear mechanisms. Results show that CoF initially increases rapidly to 0.4, this is then followed by a plateau region that finishes in a sudden step decrease in CoF following which CoF rises steadily. This behaviour is shown to be characteristic and interrupted tests are presented to allow elucidation of the wear scar at different stages in the lifetime and thus aid an understanding of the mechanisms of degradation which control the tribological behaviour.